The effect of humoristic vs. dramatic animation-based warnings: A study on acceptance and risk perception. (September 2014) - Duarte, Emília; Noriega, Paulo; Calhandro, Ana; Rebelo, Francisco
This exploratory research compared participants' (N=60) perception of several aspects and preference of two animation-based warnings which differ on the finale (dramatic versus humoristic). The warnings' purpose is to alert to the hazard of falling onto the train tracks when standing near the edge of the platform, at a subway station. The main difference between both finales rests on how the consequences of the fall are depicted. In the dramatic finale, the main character is 'sacrificed'; he/she suffers severe or deadly injuries (blood). In the humoristic one, the main character survives the crash and is seen sliding down the front screen with a silly expression on its face. The dramatic finale was the most preferred. The warning with the dramatic finale received significantly higher ratings than the one with the humoristic finale regarding attention capture, understandability, explicitness and the inverse for willingness to comply. No statistically significant differences were found for risky behavior, hazard perception, injury likelihood and severity. Implications for the design of animation-based warnings are discussed.